Phraseological units and their types in the English language - Shamsiddinova Gulnoza Vasliddin qizi (Genius Journals, 2022)
Phraseological units are considered a subsystem of language. Phraseological units cannot be freely made up in speech but are reproduced as ready-made units. The lexical components in phraseological units are stable and they are non-motivated i.e its meaning cannot be deduced from the meaning of its components and they do not allow their lexical components to be changed or substituted.
Keywords: Phraseology; fusions; classification